Mathematical Modeling of the Inhibition Kinetics of Malachite Green Decolorization by Staphylococcus aureus - Manogaran, Motharasan; Azni, Wan Yudreina Yudryk Wan; Habib, Nur Muhamad Syahir Abdul; Yasid, Nur Adeela (Journal of Environmental Microbiology and Toxicology, 2022)
Basic Green 4 or Malachite Green (MG) is an important dye that found great usage in controlling fish pathogens. The use of MG has been banned but developing, and third-world countries still found applications for this dye. Bioremediation of dyes using microorganisms is on the rise. The ability to accurately predict the rate of bioremediation relies upon the gathering of the accurate rate of decolourisation, which is often inhibited at high concentrations of the toxicant. Various secondary models such as Monod, Haldane, Teissier, Aiba, Yano and Koga, Hans-Levenspiel, Webb and the Luong models were utilized to fit the specific decolourisation rate, and most of them show visually acceptable fitting except Monod and Teissier. The best model based on statistical analysis was Hans-Levenspiel with the highest value for the adjusted coefficient of determination and the lowest values for RMSE, AICc, HQC and BIC and the closest value to 1.0 for accuracy and bias factors. The Hans-Levenspiel model was found to conform to normality tests and is adequate to be used to fit the experimental data. The normality tests carried out using tests such as the Kolmogorov-Smirnov, Wilks-Shapiro and the D'Agostino-Pearson omnibus K2 test shows that the model pass the normality tests with p >0.05 for all normality tests carried out. The experimental data obtained indicates that Malachite Green is toxic and slows down the rate of decolourisation at higher concentrations. The maximum MG specific biodegradation rate (qmax), half-saturation concentration (KS), maximum allowable MG concentration (Sm), and the shape factors (n and m) were 0.136 h-1, 0.56 mg/L, 2691 mg/L, -33.31 and 35.12, respectively. The parameters obtained from this exercise can be utilized to model the bioremediation of MG in the future.